Formulating the legal and institutional framework for elimination of terrorism financing in Malaysia (FRGS16-012-0511) - Zul Kepli, Mohd Yazid; Zulhuda, Sonny (2019)
This is the full report for 'FORMULATING THE LEGAL AND INSTITUTIONAL FRAMEWORK FOR ELIMINATION OF TERRORISM FINANCING IN MALAYSIA'. This study has examined the current legal and institutional framework pertaining to anti-terrorism financing, assessed the adequacies and inadequacies of the legal mechanism pertaining to the combating of terrorism financing in Malaysia, examined institutional framework concerning scope of duties etc in other jurisdictions and proposed recommendations for a new policy pertaining to measures to counter terrorism financing in Malaysia. The research has been conducted using qualitative method, which includes a mixture of research methods such as SWOT analysis of related laws, rules and regulations, focus group discussions, semi structured interviews with relevant stakeholders and comparative analysis with other relevant jurisdictions. It aimed to assess the effectiveness of current legal framework pertaining to terrorism financing such definition, changing methods, disruption techniques, and other legal issues. The outcome of this research (to propose the establishment of a comprehensive legal framework to combat terrorism financing) has been achieved.